PTEN: The Potential Therapeutic Target of Diabetes Mellitus - Ni Made Wiasty Sukanty; I Putu Bayu Agus Saputra; Lina Yunita (P2M Politeknik Pertanian Negeri Samarinda, 2023)
Diabetes mellitus is a metabolic disease characterized by high blood glucose levels. The cause of glucose control failure is decreased insulin production by pancreatic β-cells and insulin resistance. Both lead to the obstacle of glucose uptake into cells. The mechanism of glucose uptake into cells is crucial in carbohydrate metabolism. This mechanism aims to produce energy in the form of ATP. The main signaling pathway after the process of glucose uptake is the PI3K/Akt pathway. This pathway involves many proteins activated by phosphorylation mechanisms. One of the proteins involved in this pathway is PTEN, a PI3K regulator. PTEN activity can dephosphorylate PI3K so that the insulin signaling pathway becomes blocked and glucose cannot be uptaken into cells. It causes blood glucose levels to increase. The role of PTEN in inhibiting the PI3K/Akt pathway seems to be a crucial matter to observe. By inhibiting PTEN activity, the insulin signaling pathway is expected to work properly. We have searched, read, analyzed, and summarized various studies regarding the potential of PTEN to reduce diabetes mellitus cases. In some research articles, the use of active compounds and therapy using stem cells to inhibit PTEN activity has shown good progress in the insulin signaling pathway. Based on these, it can be an option to make PTEN a target for diabetes mellitus therapy.